Missed nursing care, the related organizational factors, and strategies for decreasing it from the viewpoints of nurses in university-affiliated hospitals of Birjand in 2019-2020 - Seyed Hasan Ghorbani; Hadi Ahmadi Chenari; Elnaz Yazdanparast; Zohreh Javanmard; Malihe Davoudi (Wolters Kluwer Medknow Publications, 2023)
Background: For many reasons, some care services may be missed. This study was conducted to investigate missed care, the related factors, and solution for decreasing them. Materials and Methods: A descriptive, cross-sectional study was performed on 122 nurses. A multi-part tool was used to gather information, which included demographic information, the Missing Nursing Care and Related Organizational Factors, and Missed Nursing Care Reduction Strategies Questionnaire. Descriptive and inferential statistical tests including ANOVA, independent t-test, and the Pearson correlation were used. Results: The mean score (SD) of the Missing Nursing Care Questionnaire was 82.04 (8.50); thus, the amount of missed nursing care is very high. Additionally, the mean score (SD) of the Organizational Factors Questionnaire related to it was 30.98 (9.35). Considering the maximum score of the questionnaire (80), the role of organizational factors in the incidence of missing nursing care is relatively moderate. There was also a weak and inverse correlation between organizational factors and missed nursing care (r = −0.30, p < 0.01, df = 120). Based on the results, increasing the number of nurses and their level of knowledge has the greatest 67.21 (%) and least 34.42 (%) impact on reducing the incidence of missed nursing care. Conclusions: According to the results, the prevalence of missed nursing care was high. However, the contribution of organizational factors to it is relatively little. This suggests that from the perspective of nurses, factors other than organizational factors related to the workplace can lead to missing care.